2013
DOI: 10.11648/j.ajce.20130103.14
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Steel Fiber on Some Mechanical Properties of Self Compacting Concrete

Abstract: Self compacting concrete (SCC) is compacting itself alone due to its self-weight and is filled almost completely while flowing in the formwork. In structural members with high percentage of reinforcement ,it fills also completely all voids and gaps. The purpose of presented research is to investigate, the fresh properties of Steel Fiber SCC and the hardened properties. Fresh properties comprising flow ability, passing ability, and viscosity related segregation resistance. Hardened properties comprising compres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 12 publications
0
37
0
9
Order By: Relevance
“…2, there is considerable conflicting evidence on the effect of fiber for measured strength at a given fiber factor. Some investigators found negligible effects [11,12,30,31], a number of them stated that the ratio of (CS SFR /CS plain ) is improved [4,13,16,[32][33][34] Güneyisi et al [13] Khaloo et al [3] Fig. 2, it can be concluded that the fiber factor is significantly influence the compressive strength.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…2, there is considerable conflicting evidence on the effect of fiber for measured strength at a given fiber factor. Some investigators found negligible effects [11,12,30,31], a number of them stated that the ratio of (CS SFR /CS plain ) is improved [4,13,16,[32][33][34] Güneyisi et al [13] Khaloo et al [3] Fig. 2, it can be concluded that the fiber factor is significantly influence the compressive strength.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…GEP modelinin eğitim, test ve doğrulama kümelerinde NY, C, SD, S, D max , K, A, SA, V f , L f ve d f değerleri girdi olarak kullanılırken, f yçd değerleri çıktı olarak kullanılmıştır. Modelde, bilimsel literatür [16][17][18][19][20]'den elde edilen 137 deney sonucundan, 91 tanesi eğitim için, 46 tanesi de test için, geriye kalan eğitim ve test kümesinde kullanılmayan bilimsel literatür [21][22][23]'den elde edilen 49 tane deney sonucu da doğrulama için kullanılmıştır. Modelde kullanılan girdi ve çıktı verileri ile ilgili daha fazla bilgi bilimsel literatürler [16][17][18][19][20][21][22][23]'den elde edilebilir.…”
Section: Gen Ifadeli Programlama Modeliunclassified
“…Bu çalışmada, çelik fiberle güçlendirilmiş silis dumanı içeren betonların f çyd değerlerinin tahmininde kullanılan GEP modelinin eğitim, test ve doğrulama kümelerinde, farklı literatürden [16][17][18][19][20][21][22][23] elde edilen numunelerin yaşı, beton karışım miktarları ve çelik fiberin özellikleri girdi değişkenleri olarak ve f çyd deney sonuçları da çıktı değişkeni olarak kullanılmıştır. Bu deneysel verilerdeki numune yaşı, beton karışım miktarları ve f çyd değerlerinin karşılaştırılması Şekil 3'te verilmiştir.…”
Section: Bulgular Ve Tartişmaunclassified
See 1 more Smart Citation
“…Impact energy of concrete was found to be slightly more when hooked end steel was used compared to crimped steel. The effect of steel fibre on some mechanical propertied of self compacting concrete was studied by Abbas AL-Ameeri [20] purposed to investigate the fresh properties of steel fibre SCC and the hardened properties. He drew to the conclusion that the flow ability as well as blocking ratios both decreases with the increase in steel fibre also the slump flow time and Vfunnel flow time increase with the increase in steel fibre.…”
Section: Experimental Studies On Strength Propertiesmentioning
confidence: 99%